PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN HOTEL JW MARRIOTT SURABAYA - HARIYANTO, DEDY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:Economic development in Surabaya is increasing competition in the business world, hospitality services business is one of them. JW Marriott Hotel Surabaya is considered a five-star hotel with various facilities and services offered to customers. However, the competition in the five-star hotel bussiness is increasing and customer satisfaction is the key to win the market. Good quality service is very important to make the customer feel satisfied so they will come back. The purpose of this study was to determine the impact of servqual towards customer satisfaction at the JW Marriott Hotel Surabaya.The approach in this research is quantitative, and this type of research is to examine causalityl relationship variables. Population in this research isthe customer JW Marriott Hotel Surabaya, the sampling technique using accidental sampling. Data collection method used was observationand questionnaires. The method of analysis used in this study is multiple linear regression analysis. Keywords:servqual, satisfaction, and hotel.